A Multilevel Analysis of the Impact of Unit Tightness vs. Looseness Culture on Attitudes and Behaviors in the Workplace - Di Santo, Daniela; Talamo, Alessandra; Bonaiuto, Flavia; Cabras, Cristina; Pierro, Antonio (Frontiers in Psychology, 2021)
This study examines the impact of work unit-level perceived Tightness vs. Looseness (T-L) culture on individual-level perceived stress, intention to leave, organizational deviance, job satisfaction, effort investment, and organizational commitment. Using quantitative cross-sectional data (N = 417) collected from preexisting work units (N = 57) in different organizations in Italy, multilevel analysis results revealed that a perceived cultural tightness at the unit level was significantly and positively related to individual-level job satisfaction, effort investment, and organizational commitment and significantly and negatively related to individual-level stress, intention to leave, and organizational deviance. The findings suggest that organizations should promote a culture of tightness to positively influence employee attitudes and behaviors. Limitations and recommendations for future research are discussed.